Plant Propagation by Tissue Culture Volume 1. The Background - George, Edwin F.; Hall, Michael A.; De Klerk, Geert-Jan (Springer Netherlands : Imprint: Springer, 2008)
It is now more than twenty years since the first edition of this work appeared and nearly fifteen since the second. Whilst much of the information in those editions has stood the test of time, inevitably, because of the pace of research, a new edition is clearly timely. This is true, not only because many more species have been the subject of propagation studies, but because the background to the field - with which this volume deals - has changed almost out of all recognition. In particular, our knowledge of plant development, genetics physiology, biochemistry and molecular biology has expanded exponentially - often through work on mutants of Arabidopsis - and opened up many new avenues for the plant propagator to explore. Equally, the commercial significance of plant propagation has increased significantly. As an example, in the second edition there was a single chapter on plant growth regulators - in this there are three, reflecting the fact that not only is there more information on those PGRs we recognised in 1993, but that several new ones are now known. Equally, fifteen years ago we knew little of the molecular basis of plant development e. g. flower and shoot development, in this edition it has merited a whole chapter, much of which relates to discoveries in the last decade. Because of these factors, it was felt that a different approach was required for this edition.